Adaptive capacity and social-ecological resilience of coastal areas: A systematic review. (1st May 2019) - Ferro-Azcona, Hakna; Espinoza-Tenorio, Alejandro; Calderón-Contreras, Rafael; Ramenzoni, Victoria C.; Gómez País, Maria de las Mercedes; Mesa-Jurado, Maria Azahara
Abstract: Establishing protected areas constitutes one of the main strategies for the conservation of marine and coastal ecosystems. Increasing risks associated with environmental change along with highly degraded coastal ecosystems encompass complex management challenges for the long-term sustainability of these landscapes. This article aims to explore the role of protected areas in past and ongoing community adaptation to the compounded effects of climatic and anthropogenic change. A literature review of published articles is conducted through systematic queries of the bibliographic database Web of Sciences, and by comparing adaptation and social-ecological resilience processes within and out of coastal protected areas. Findings underscore the absence of specific studies that target these topics inside protected areas, highlighting a geographic bias towards research largely carried out in developed countries. Results also indicate the current need for management practices within protected areas to adopt more participatory, comprehensive, and flexible approaches. Protected areas not only promote the conservation and provision of ecosystem services but are also key in building coastal communities' adaptive capacity and resilience in face of future scenarios. Highlights: 192 papers were reviewed, from research in marine and coastal protected and non-protected areas. The review distinguishes between Social-Ecological Resilience and Adaptive capacity to climate change and risks. Countries with high vulnerability to climate change are underrepresented in the literature. There is a predominance of studies on policy formulation with respect to measurement.